Clearance flow patterns and pressure distribution of a pump-turbine: Measurement and simulation of a rotating disk flow - Hou, Xiaoxia; Liu, Herui; Cheng, Yongguang; Liu, Ke; Liu, Demin; Chen, Hongyu (Frontiers in Energy Research, 2022)
The clearance flow patterns and pressure distribution determine the clearance axial hydraulic thrust of a pump turbine, which has a substantial impact on the unit axial imbalance. However, due to the tiny size and complex shape of the clearance flow channel, there is no detailed description of the flow patterns and pressure characteristics. In this study, we conducted a model test with particle image velocimetry (PIV) measurements and CFD simulation of a rotating disk flow that was a simplified model of the pump-turbine clearance flow. It is shown that a typical Batchelor flow is formed in the clearance region, demonstrating a “core region + double-boundary layers” distribution for the circumferential velocity along the clearance height direction; the core region rotates at a speed of only around 41–42% of the rotating disk speed and is independent of the clearance inlet pressure and clearance height. Driven by centrifugal force, the flow is radially outward around the rotating disk, while inward around the stationary disk in the meridian section, showing secondary flow vortices. The pressure in the clearance region has a circumferentially symmetric and radially quadratic distribution. Based on the liquid differential equilibrium equation and core region circumferential velocity, the pressure and clearance axial hydraulic thrust in the clearance region can be expressed as a function of the clearance inlet pressure and the square of the runner rotating speed. These findings can be used to investigate axial force imbalance issues of the pump-turbine unit.